The Semiotic Construction of a Holiday Country: The case of Croatia - Bertoša, Mislava (Array, 2012)
Using Croatia as an example, this article analyses modes of constructing a country as a tourist destination, from a semiotic perspective. From this perspective, tourism may be viewed as a practice that contrasts with everyday life. It encompasses dimensions including the following aspects of the journey: travel, absence of obligation, entertainment, and relaxation. To be a tourist and to practice tourism involves dislocation and transferring from one´s place of residence to another place. This "other place" is constructed and represented to potential tourists as a "tourist destination". The article focuses on the contents and targets of the tourist´s travel, or, semiotically speaking, their valorizations. The principal starting point is the typology of valorizations elaborated by Floch. A place becomes a tourist destination when it has been semiotically valorized (i.e., when it is ascribed a certain value). This value may be represented to potential travelers/tourists via different modes of expression including catalogues, brochures, websites and advertisments. The analysis has been thematically narrowed to the field of Croatian cultural heritage, with particular reference to history, art, architecture, monuments, and festivals. The subject of the analysis is a brochure published by the Croatian National Tourist Board in 2009. The authors examine semiotic strategies and modes of ascribing values and meanings to places that are presented as historical and cultural destinations. They take into consideration both verbal and visual modes, and identify the types of semiotic valorizations that have been used in the construction of a place as a tourist target.